Alpha-tomatine synergises with paclitaxel to enhance apoptosis of androgen-independent human prostate cancer PC-3 cells in vitro and in vivo - Lee, Sui-Ting; Wong, Pooi Fong; Hooper, J.D.; Mustafa, Mohd Rais (2013)
Alpha (Î±)-tomatine, a major saponin found in tomato has been shown to inhibit the growth of androgen-independent prostate cancer PC-3 cells. The effects of Î±-tomatine in combination with the chemotherapeutic agent paclitaxel against PC-3 cells were investigated in the present study. Combined treatment with a sub-toxic dose of Î±-tomatine and paclitaxel significantly decreased cell viability with concomitant increase in the percentage of apoptotic PC-3 cells. The combined treatment, however, had no cytotoxic effect on the non-neoplastic prostate RWPE-1 cells. Apoptosis of PC-3 cells was accompanied by the inhibition of PI3K/Akt pro-survival signaling, an increase in the expression of the pro-apoptotic protein BAD but a decrease in the expressions of anti-apoptotic proteins, Bcl-2 and Bcl-xL. Results from a mouse xenograft model showed the combined treatment completely suppressed subcutaneous tumor growth without significant side effects. Consistent with its in vitro anti-cancer effects, tumor materials from mice showed increased apoptosis of tumor cells with reduced protein expression of activated PI3K/Akt. These results suggest that the synergistic anti-cancer effects of paclitaxel and Î±-tomatine may be beneficial for refractory prostate cancer treatment.